2017
DOI: 10.3238/arztebl.2017.0838
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Pneumonia in Adults

Abstract: Major considerations include appropriate risk stratification and the implementation of a management strategy adapted to the degree of severity of the disease, along with the establishment of structured follow-up care and secondary prevention, especially for patients with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 56 publications
(54 reference statements)
0
53
0
18
Order By: Relevance
“…Pneumonia is an extremely common, yet exceedingly dangerous condition that makes up 423,000 emergency room visits and is the 8th leading cause of death in the United States, according to the CDC [1]. Inpatient community-acquired pneumonia (CAP) treatment is often empiric and laboratory testing may not result in a definite organism [2]. It has been demonstrated that the microbial etiology of roughly 30%-60% of CAPs treated in the inpatient setting remains unidentified [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia is an extremely common, yet exceedingly dangerous condition that makes up 423,000 emergency room visits and is the 8th leading cause of death in the United States, according to the CDC [1]. Inpatient community-acquired pneumonia (CAP) treatment is often empiric and laboratory testing may not result in a definite organism [2]. It has been demonstrated that the microbial etiology of roughly 30%-60% of CAPs treated in the inpatient setting remains unidentified [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The newly onset lower respiratory syndromes with new lung in ltrate on chest radiograph, especially when supported by laboratory ndings and compatible physical examinations, is considered indicative for diagnosing community-acquired pneumonia (CAP) [11]. The clinical and radiological manifestations of COVID-19 may have some overlap with the manifestations of CAP caused by other pathogens, such as In uenza-A viral, Mycoplasma pneumoniae and Chlamydia pneumoniae and Streptococcus pneumoniae [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sie stellt ein zunehmendes Gesundheitsproblem der immer älter werdenden Bevölkerung dar. Mit jeder Lebensdekade steigt die Inzidenz der Erkrankung [2]. Gleichzeitig kommt es alterskorreliert zu wachsenden Mortalitätsraten [3].…”
Section: Introductionunclassified